Predictive value of individual serum neurofilament light chain levels in short-term disease activity in relapsing multiple sclerosis - Solís-Tarazona, Luis; Raket, Lars Lau; Cabello-Murgui, Javier; Reddam, Salma; Navarro-Quevedo, Silvia; Gil-Perotin, Sara (Frontiers in Neurology, 2024)
The assessment of serum neurofilament light chain (sNFL) has emerged as a diagnostic and prognostic tool in monitoring multiple sclerosis (MS). However, the application of periodic measurement in daily practice remains unclear.Objective: To evaluate the predictive value of individual sNFL levels in determining disease activity in patients with relapsing MS (RMS).In this two-year prospective study, 129 RMS patients underwent quarterly sNFL assessments and annual MRI scans. The study analyzed the correlation between individual NFL levels and past, current, and future disease activity. Group-level Z-scores were employed as a comparative measure.Results: Among the 37 participants, a total of 61 episodes of disease activity were observed. sNFL levels proved valuable in distinct ways; they were confirmatory of previous and current clinical and/or radiological activity and demonstrated a high negative predictive value for future 90-day activity. Interestingly, Z-scores marginally outperformed sNFL levels in terms of predictive accuracy, indicating the potential for alternative approaches in disease activity assessment. In our cohort, sNFL cut-offs of 10.8 pg/ml (sensitivity 27%, specificity 90%) and 14.3 pg/ml (sensitivity 15%, specificity 95%) correctly identified 7 and 4 out of 26 cases of radiological activity within 90 days, respectively, with 14% and 15% false negatives. These findings emphasize the importance of determining appropriate sNFL thresholds for clinical decision-making.individual sNFL levels may potentially confirm prior or current disease activity and predict short-term future radiological activity in RMS. These findings underscore its periodic measurement as a valuable tool in RMS management and decision-making, enhancing the precision of clinical evaluation in routine practice.